Kurma, Kola and Kuri as community concepts: Patrilineage, deities, and inside-outside dichotomy among the Rana Tharus - Gurung, Ganesh Man; Kittelsen, Tove C (Occasional Papers in Sociology and Anthropology, 2008)
DOI: 10.3126/opsa.v5i0.1096 Occasional Papers in Sociology and Anthropology Vol.5 1996 p.78-93